2020
DOI: 10.9745/ghsp-d-19-00347
|View full text |Cite
|
Sign up to set email alerts
|

Two-Way Short Message Service (SMS) Communication May Increase Pre-Exposure Prophylaxis Continuation and Adherence Among Pregnant and Postpartum Women in Kenya

Abstract: a,g for the PrIYA Program Team We evaluated a 2-way short messaging service (SMS) communication platform to improve continuation of preexposure prophylaxis (PrEP) for HIV prevention among Kenyan pregnant and postpartum women who initiated PrEP within routine maternal child health and family planning clinics. SMS increased support for PrEP, provided opportunities for dialogue beyond the clinic, and enabled women to ask and receive answers in real-time, which facilitated continued PrEP use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“… 8 Both DATs have been studied in sub-Saharan Africa to assess their effectiveness at improving ART adherence, viral load suppression and clinic attendance. 9–13 In Uganda, trials that included RTMM technology linked to SMS reminders showed high acceptability and increased positive habits towards ART adherence. 14 A study conducted in South Africa found that being monitored in real-time, motivated 80% of participants to take their ART.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Both DATs have been studied in sub-Saharan Africa to assess their effectiveness at improving ART adherence, viral load suppression and clinic attendance. 9–13 In Uganda, trials that included RTMM technology linked to SMS reminders showed high acceptability and increased positive habits towards ART adherence. 14 A study conducted in South Africa found that being monitored in real-time, motivated 80% of participants to take their ART.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies were carried out in Kenya [31][32][33][34], two in Ghana [29,35], one in South Africa [36], two in Uganda [37,38], and one in Tanzania [39]. Five studies were RCTs [29,33,34,37,38], three were evaluation and pre-post design studies [31,32,39], and two were mixed PLOS ONE methods/cross-sectional studies [35,36]. Seven studies occurred in a hospital setting [31][32][36][37][38], one was school-based [29] and two were community-based [35,39] (Table 1).…”
Section: Study Setting and Designmentioning
confidence: 99%
“…Five studies were RCTs [29,33,34,37,38], three were evaluation and pre-post design studies [31,32,39], and two were mixed PLOS ONE methods/cross-sectional studies [35,36]. Seven studies occurred in a hospital setting [31][32][36][37][38], one was school-based [29] and two were community-based [35,39] (Table 1).…”
Section: Study Setting and Designmentioning
confidence: 99%
“…Many researchers have emphasized that SMS plays a vital role in fields of health communication, medicine treatment, momentous emergency events, etc. As an effective tool and intervention method, a series of studies have revealed the positive effects of sending health information by one-way or an interactive way for pre-exposure prevention [4]. SMS can help people manage their health [5,6] and prevent disease [7,8].…”
Section: Literature Review: Sms Application Areasmentioning
confidence: 99%